Pressurized intraperitoneal aerosol chemotherapy (PIPAC) - Moreira Grecco, Alejandro; Delgadillo, Xavier; Suárez Anzorena, Francisco; Sarotto (h), Luis E. (Revista Argentina de Cirugía, 2021)
Pressurized intraperitoneal aerosol chemotherapy (PIPAC) is a therapeutic option for patients with unresectable peritoneal carcinomatosis. The steps and the surgical technique of the PIPAC technique are thoroughly described.